Research on credit card anti-fraud based on data mining - Zhang, Haolun (Transactions on Computer Science and Intelligent Systems Research, 2024)
The research topic of this paper is the field of credit card anti-fraud, using the European credit card data of the past two days in September 2018 for research, describing the data distribution through exploratory data analysis, data normalization, and finally using logistic regression for anti-fraud identification prediction.